2017
DOI: 10.1093/sf/sow097
|View full text |Cite
|
Sign up to set email alerts
|

Hypermobility, Destination Effects, and Delinquency: Specifying the Link between Residential Mobility and Offending

Abstract: funding from 23 other federal agencies and foundations. Special acknowledgment is due to Ronald R. Rindfuss and Barbara Entwisle for assistance in the original design. Information on how to obtain the Add Health data files is available on the Add Health website (http://www.cpc.unc.edu/addhealth). No direct support was received from grant P01-HD31921 for this analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 46 publications
2
26
3
Order By: Relevance
“…29 However, in a subsequent study, Vogel et al used fixed-effects regression to estimate within-person associations and reported that although a binary indicator of mobility was not associated with delinquency, greater frequency of mobility was positively associated with delinquency. 30 Although these studies argue against a causal effect of mobility on behavioural outcomes, they have generally focused on outcomes occurring immediately following, or contemporaneous with, adolescent mobility. Additional research is needed to assess the causality of longer-term prospective associations between residential mobility and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, in a subsequent study, Vogel et al used fixed-effects regression to estimate within-person associations and reported that although a binary indicator of mobility was not associated with delinquency, greater frequency of mobility was positively associated with delinquency. 30 Although these studies argue against a causal effect of mobility on behavioural outcomes, they have generally focused on outcomes occurring immediately following, or contemporaneous with, adolescent mobility. Additional research is needed to assess the causality of longer-term prospective associations between residential mobility and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…First, the census tract is the geographic aggregation that most closely approximates a neighborhood and is used most frequently in studies of neighborhood effects (Sampson 2002). Second, recent studies examining neighborhood effects on youth outcomes in the NLSY97 have consistently relied on tract-level measures of neighborhood characteristics (e.g., Vogel and South 2016;Vogel et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Emerging research suggests that characteristics of sending and receiving neighborhoods may be more consequential than the simple act of moving (Sharkey and Sampson 2010;Vogel et al 2017). This research has primarily focused on the effects of moving into and out of deprived neighborhoods, as prolonged exposure to socioeconomic disadvantage has been consistently linked to detrimental outcomes in later life (Ellen and Turner 1997;Leventhal and Brooks-Gunn 2000;Clark and Morrison 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is not possible to know if these strategies kept youth safe, but it is clear that they often compromised young men's education. This builds on our understanding of mobility, which is known to be linked to academic challenges and delinquency, but these outcomes have also been linked with factors associated with mobility, such as poverty (for a full review, see [57]). It is also not the only cause of mobility, which is often coerced by the justice and education systems [58].…”
Section: Systemic Constraints On Traditional Family and Youth Strategmentioning
confidence: 99%